월 슬라이드 운동과 어깨뼈 정렬 운동이 어깨뼈 아래쪽돌림 증후군의 어깨뼈 위쪽돌림근 근활성도와 위등세모근 압력 통증 역치에 미치는 영향 - 김동열; Dongyeol Kim; 김경; Kyoung Kim; Minseo Kim; 임상철; Sangcheol Im (Journal of the Korean Society of Integrative Medicine, 2025)
Purpose : This study was conducted to investigate the immediate effects of wall slide and scapular setting exercises on scapular upward rotator muscle activity and upper trapezius pressure pain threshold in subjects with scapular downward rotation syndrome. Methods : Thirty adult men with scapular downward rotation syndrome were randomly assigned to either a wall slide (n= 15) or a scapular setting (n= 15) exercise group. Each participant performed the wall slide exercise and scapular setting exercise for equal periods of 30 min. Scapular upward rotator muscle activity and pressure pain threshold of the upper trapezius muscle were measured using a wireless surface electromyography device and an electronic algometer, respectively. Results : Comparison within groups showed that the wall slide exercise group exhibited a significant decrease in the upper trapezius muscle activity (p<.05) but a significant increase in the serratus anterior muscle activity and upper trapezius pressure pain threshold (p<.05). The scapular setting exercise group exhibited significantly increased muscle activity of the serratus anterior (p<.05). Comparison between groups showed that the wall slide exercise group exhibited significantly decreased muscle activity of the upper trapezius compared with the scapular setting exercise group (p<.05) and significantly increased muscle activity of the serratus anterior and pressure pain threshold of the upper trapezius (p<.05). Conclusion : The wall slide exercise decreased the muscle activity of the upper trapezius and increased the muscle activity of the serratus anterior and the pressure pain threshold of the upper trapezius in subjects with scapular downward rotation syndrome. The scapular setting exercise increased the muscle activity of the serratus anterior. Both exercises were effective for subjects with scapular downward rotation syndrome, with the wall slide exercise being more effective than the scapular setting exercise.